2010
DOI: 10.1074/jbc.m110.159855
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Poly(ADP-ribose) Recognition by the Multizinc Binding Domain of Checkpoint with Forkhead-associated and RING Domains (CHFR)

Abstract: Cellular stress in early mitosis activates the antephase checkpoint, resulting in the decondensation of chromosomes and delayed mitotic progression. Checkpoint with forkheadassociated and RING domains (CHFR) is central to this checkpoint, and its activity is ablated in many tumors and cancer cell lines through promoter hypermethylation or mutation. The interaction between the PAR-binding zinc finger (PBZ) of CHFR and poly(ADP-ribose) (PAR) is crucial for a functional antephase checkpoint. We determined the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 28 publications
3
53
0
Order By: Relevance
“…We first expressed and purified the recombinant GST-ECT2 BRCT domain in vitro and performed in vitro binding assay by incubating recombinant GST-ECT2 BRCT with PAR. Since CHFR directly interacts with PAR via its C-terminal PBZ motif, [16][17] we used GST and recombinant CHFR as the negative and positive control in this binding assay, respectively. Purified recombinant proteins were dot-blotted on the nitrocellulose membrane after incubation with PAR.…”
Section: Resultsmentioning
confidence: 99%
“…We first expressed and purified the recombinant GST-ECT2 BRCT domain in vitro and performed in vitro binding assay by incubating recombinant GST-ECT2 BRCT with PAR. Since CHFR directly interacts with PAR via its C-terminal PBZ motif, [16][17] we used GST and recombinant CHFR as the negative and positive control in this binding assay, respectively. Purified recombinant proteins were dot-blotted on the nitrocellulose membrane after incubation with PAR.…”
Section: Resultsmentioning
confidence: 99%
“…His-tagged human PARP1 was expressed in bacteria and purified by Ni-NTA affinity resin. PAR was synthesized and purified as described previously except for the following modifications (49). PAR was synthesized in a 20-mL incubation mixture containing 100 mM Tris·HCl pH 7.8, 10 mM MgCl 2 , 1 mM NAD + , 10 mM DTT, 60 μg calf thymus histone, 50 μg octameric oligonucleotide GGAATTCC, and 2 mg PARP1.…”
Section: Methodsmentioning
confidence: 99%
“…Since CHFR and APLF are known PAR-binding proteins, which bind PAR via their PBZ motifs (Ahel et al 2008;Li et al 2010;Oberoi et al 2010), we used GST, recombinant CHFR, and APLF PBZ motifs as negative and positive controls, respectively, to screen PAR-binding domains. We examined 19 FHA or BRCT domains and found that two FHA domains (from PNKP and APTX), two BRCT domains (from Ligase4 and XRCC1), and an FHA-BRCT fusion domain (from NBS1) interacted with PAR (Fig.…”
Section: A Set Of Brct and Fha Domains Binds Parmentioning
confidence: 99%